The effects of Aboriginal tertiary students’ perceived experiences of racism and of cultural resilience on educational engagement - Gibbs, Jordan; Paradies, Yin; Gee, Graham; Haslam, Nicholas (The Australian Journal of Indigenous Education, 2022)
Racism pervasively impacts the lives of Aboriginal and Torres Strait Islander peoples and is a substantial barrier to accessing, engaging and succeeding within secondary education. Cultural resilience and support have been identified as critical to Aboriginal success within racist institutions. However, research examining experiences of racism and cultural resilience among Aboriginal tertiary students is limited. This study explored the relationship between racism, cultural resilience, and educational engagement and academic outcomes in a sample of these students (N = 63). We proposed that higher perceived racism would be associated with lower engagement and academic outcomes. The study also developed a new measure of Aboriginal tertiary students’ experience of racism during their studies, which demonstrated good reliability and validity. Experiencing racism was associated with perceiving a less supportive learning environment, and with lower learning outcomes, developmental outcomes and overall student satisfaction.